Five-year Variations in Air Pollutant Emissions with Ultra-low Emission Retrofits in a 660 MW Coal-fired Power Unit - Li, Zhiyong; Ren, Zhuangzhuang; Cao, Chengjing; Liu, Chen; Zhai, Zhen; Liu, Jixiang; Zhan, Ziyi; Huang, Changtao; Chen, Lan; Yuan, Hongdan (Aerosol and air quality research, 2023)
China has enacted the ultra-low emission (ULE) transform in coal-fired power plants. Various studies have focused on the model simulation of pollutant emission variations on a national scale, while the specific data for a concrete generation unit was still lacking. We deployed a five-year online data collection campaign in a 660 MW unit to investigate the durative emission reductions of dust, NO x , and SO 2 , and increases in pollutant removal efficiencies. The result indicated that a time slag appeared between the ULE execution and meeting discharge standards. Since the ULE implementation in late 2014, the pollutant emissions exhibited a decreasing trend, while it was not until 2016 that the emission amounts reached the ULE standards with the actual emissions of 30.7 ± 4.43, 12.3 ± 3.49, and 1.80 ± 0.425 mg m −3 for NO x , SO 2 , and dust, respectively. It was particularly pointed out that emissions increased again in 2017 though they still met the ULE standards, indicating the comprehensive consideration should be taken between the emission reductions and high cost of the ULE policy. What’s more, the ULE transformation weaken the correlation between pollutant emissions (in mg m −3 ) and corresponding removal efficiencies of control devices, evidencing the pollutant emissions received complex impacts from coal components, emission control technologies and devices, and so on. More practical emission factors (EFs) expressed in kg h −1 and g MWh −1 relative to the ULE were updated and in this study. Unlike EFs expressed in mg m −3 , the most decreases of EFs in kg h −1 and g MWh −1 in 2015 by more than 97.0% compared to 2014 for three air pollutants arisen from reasonable air supply or enhancement in thoroughness of coal combustion.